Recovering 3-D Shape: Roles of Absolute and Relative Disparity, Retinal Size, and Viewing Distance as Studied with Reverse-Perspective Stimuli. (April 2013) - Dobias, Joshua J; Papathomas, Thomas V
When viewing reverspective stimuli, data-driven signals such as disparity, motion parallax, etc, help to recover veridical three-dimensional (3-D) shape. They compete against schema-driven influences such as experience with perspective, foreshortening, and other pictorial cues that favor the perception of an illusory depth inversion. We used three scaled-size versions of a reverspective to study the roles of retinal size, binocular disparity, and viewing distance—that influences both vergence and accommodation—in recovering the true 3-D shape. Experiment 1 used three conditions, in each of which a parameter was kept fixed across the three stimulus sizes: (a) fixed retinal size, (b) fixed viewing distance, (c) fixed disparity. The predominance of the veridical percept was recorded. Generally, the illusion strength was the same when the viewing distance was fixed, despite significantly different disparities and retinal sizes; conversely, illusion strength changed significantly in fixed-disparity and fixed-retinal-size conditions. Experiment 2 confirmed the results of experiment 1b (roughly equal performances for fixed viewing distance, independent of size) for two additional distances. Viewing distance and "scaled disparity" (disparity divided by retinal size) are good predictors of the data trends. We propose that disparity scaling is supported by both mathematical and 3-D shape considerations.